Pistacia terebinthus coffee protects against thioacetamide-induced liver injury in rats - Bahcecioglu, Ibrahim Halil; Ispiroglu, Murat; Tuzcu, Mehmet; Orhan, Cemal; Ulas, Mustafa; Demirel, Ulvi; Yalniz, Mehmet; Özercan, Ibrahim H; Ilhan, Necip; Sahin, Kazim (Acta Medica, 2015)
AIM/BACKGROUND: Pistacia terebinthus is used as a coffee substitute in the East and Southern Anatolia regions of Turkey. It contains unsaturated fatty acids, tocopherols, polyphenols and carotenoids. P. terebinthus has anti-inflammatory and potential antioxidant activity. In this study we evaluated the protective effects of P. terebinthus coffee (PTC) on thioacetamide (TAA)-induced liver injury in rats. MATERIALS AND METHODS: Twenty-eight male Sprague-Dawley rats were equally randomized into four groups. Chronic liver injury was induced with TAA (100 mg/kg i.p. three times weekly). The first group of rats served as control and received only tap water (G1), and the remaining groups of rats received PTC, p.o (G2); TAA (G3); TAA plus PTC, p.o (G4), respectively. RESULTS: After 8 weeks, PTC intake significantly reduced fibrosis/inflammation scores (p PTC intake reduced transforming growth factor beta (TGF-β) concentrations in the liver (p PTC intake. DISCUSSION AND CONCLUSION: PTC intake provided beneficial effects against TAA-induced liver injury in rats. PTC probably suppresses the proinflammatory cytokines through NF-κB signaling pathway.
Keywords: Liver; Animals; zánět; Antioxidants; oxidační stres; játra; výsledek terapie; Transforming Growth Factor beta; Oxidative Stress; noxy; transformující růstový faktor beta; Treatment Outcome; experimentální cirhóza jater; Teas, Herbal; Rats, Sprague-Dawley; Inflammation; triterpeny; Liver Cirrhosis, Experimental; Male; modely nemocí na zvířatech; potkani Sprague-Dawley; antioxidancia; Thioacetamide; Disease Models, Animal; krysa rodu Rattus; thioacetamid; Triterpenes; Noxae; zvířata; mužské pohlaví; bylinné čaje; Pistacia; Rats